Improving Students’ Critical Thinking Skills Through The Use Of Pbl-Base Google Sites Learning Media And Review Students’ Collaboration Skills - Sri Wahyuni; Andan Yani; Dadan Rosana; Insih Wilujeng; Sabar Nurohman (International Journal Labs, 2024)
Human Resources (HR) must have the 4Cs (communication, collaboration, critical thinking, and creativity) to be educated in the 21st century. Initial research shows that students' ability to collaborate and think critically still needs to be improved. This research aims to determine the use of PBL-Google Sites learning media to improve critical thinking skills and review students' collaboration skills. The research method uses pre-experiment with a one-group pretest-posttest design. The research sample comprised 63 students in classes 7A and 7B of SMP Negeri 11 Yogyakarta. The instruments used are tests and non-tests. The test instrument uses pretest and posttest critical thinking skills. The non-test instrument uses observation of collaboration skills. The data analysis results show the influence of using Google Sites PBL learning media on students' critical thinking abilities. Judging from the results of the Wilcoxon test, the Sig (2-tailed) value is <0.05, namely 0.000, and there is an effect size value of -0.616, which shows that the magnitude of the effect is in a large category. Students' collaborative skills obtained an average score of 75.14, which is in the good category. Based on the results of data analysis, the Google Sites PBL model learning media can improve students’ critical thinking skills and determine students' collaboration skills.